E-business and Telecommunication Networks - Filipe, Joaquim (Springer, 2017)
This book contains the best papers of the Second International Conference on E-business and Telecommunication Networks (ICETE), which was held, in 2005, at the Microsoft Research Centre - Reading, in the UK. The conference was organized by INSTICC (Institute for Systems and Technologies of Information, Communication and Control) in collaboration with the University of Westminster/WITRC, UK. ICETE reflects a continuing effort to increase the exchange of expertise among professionals who work in the fields of e-business and telecommunication networks, including aspects related to security, wireless systems, signal processing, and all sorts of applications, who are bringing new services and technologies into the lives of ordinary consumers. The major goal of this conference was thus to bring together researchers and developers from academia and industry working in areas related to e-business to stimulate a debate with a special focus on telecommunication networks. Four simultaneous tracks were held, covering different aspects, namely: “Global Communication Information Systems and Services”, “Security and Reliability in Information Systems and Networks”, “Wireless Communication Systems and Networks” and “Multimedia Signal Processing”. Each of these tracks appealed to a global audience of engineers, scientists, business people and policy experts, interested in the research topics of ICETE. All tracks focused on specific topics of research and real world applications and relied on contributions from industry, with different solutions for end-user applications and enabling technologies, in a diversity of communication environments.